Fluorescence sentinel lymph node mapping in patients with cervical cancer - G. B. Mkrtchyan; I. V. Berlev; Yu. N. Trifanov; E. N. Kozlova; Z. N. Ibragimov; A. F. Urmancheeva; N. A. Mikaya; E. A. Ulrikh (Опухоли женской репродуктивной системы)
Objective: to assess the efficacy of fluorescence sentinel lymph node (SLN) detection with indocyanine green (ICG) in patients with cervical cancer.Materials and methods. We analyzed the results of examination and treatment in 80 patients with morphologically verified stage IA1–IIA1 cervical cancer. All patients underwent laparoscopic surgery with fluorescence SLN detection with ICG using a high-resolution infrared camera.Results. SLNs were detected in 78 out of 80 patients (97.5 %); the rate of bilateral SLN detection was 80.0 % (64 out of 80). SLNs were not identified in 2 patients only (2.5 %). The majority of SLNs (99 out of 176; 56.28 %) were located in the internal group of lymph nodes, near to the common iliac artery bifurcation. Eleven out of 80 patients (13.75 %) were found to have pelvic lymph node metastasis. SLN metastatic lesions were observed in 10 out of 80 patients (12.5 %), whereas only one participant had non-SLN metastasis. Therefore, the sensitivity of the fluorescence method with ICG was 98.75 %.Conclusion. Fluorescence SLN mapping with ICG in patients with stage IA1–IIA1 cervical cancer is an effective diagnostic method allowing SLN topical diagnosis, intraoperative restaging, and correction of the treatment strategy.